2021
DOI: 10.3389/fvets.2021.756486
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Alterations in Diarrheal Baer's Pochards (Aythya baeri)

Abstract: The structure and composition of gut microbiota correlate with the occurrence and development of host health and disease. Diarrhea can cause alterations in gut microbiota in animals, and the changes in the gut microbial structure and composition may affect the development of diarrhea. However, there is a scarcity of information on the effects of diarrhea on gut fungal composition and structure, particularly in Baer's pochard (Aythya baeri). The current study was performed for high-throughput sequencing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…In our study, a significant reduction in gut microbial abundance and diversity was observed in diarrheic Père David’s deer ( Figure 1 ). Similar data were reported in diarrheic humans ( Homo sapiens ) [ 32 ], mice ( Mus musculus ) [ 33 ], Baer’s pochards ( Aythya baeri ) [ 23 ], musk deer ( Moschus berezovskii ) [ 19 ], and giraffes ( Giraffa camelopardalis reticulata ) [ 24 ]. Thus, gut microbiota diversity reductions may be typical features in diarrheic individuals, no matter the diarrhea type or causative species.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, a significant reduction in gut microbial abundance and diversity was observed in diarrheic Père David’s deer ( Figure 1 ). Similar data were reported in diarrheic humans ( Homo sapiens ) [ 32 ], mice ( Mus musculus ) [ 33 ], Baer’s pochards ( Aythya baeri ) [ 23 ], musk deer ( Moschus berezovskii ) [ 19 ], and giraffes ( Giraffa camelopardalis reticulata ) [ 24 ]. Thus, gut microbiota diversity reductions may be typical features in diarrheic individuals, no matter the diarrhea type or causative species.…”
Section: Discussionsupporting
confidence: 75%
“…Meantime, intestinal microbial communities are often severely imbalanced in diarrheic hosts, regardless of the diarrhea cause; even gut microbiota dysbiosis may be causative for diarrhea [ 21 , 22 ]. The changes of gut microbiota were reported in diarrheic Baer’s pochards ( Aythya baeri ) [ 23 ], musk deer ( Moschus berezovskii) [ 19 ] and giraffes ( Giraffa camelopardalis reticulata ) [ 24 ]. However, to date, the gut microbiota condition in diarrheic Père David’s deer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, tissue shows diffuse expansion of lamina propria and submucosa by macrophages containing intracellular yeast forms[ 6 , 10 ]. As in our case, due to similarities in presentation, pattern of involvement and associated granulomatous inflammation, gastrointestinal histoplasmosis can mimic CD[ 6 , 14 - 17 ].…”
Section: Discussionmentioning
confidence: 80%
“…Notably, state-of-the-art renewal has revealed diseases linked to dyslipidemia including atherosclerosis, obesity and MAFLD, which are associated with variations in gut microbiota profile and the accompanied host metabolism and physiology [11][12][13][14]. Meanwhile, compelling evidences have indicated that the gut microbiota might impact lipid metabolism in blood and tissue of the body via metabolites (e.g., short-chain fatty acids, trimethylamine, secondary bile acids, indole and its derivatives) and the bacterially proinflammatory factors (e.g., extracellular vesicles, peptidoglycan, DNA, lipopolysaccharide) [15][16][17].…”
Section: Open Accessmentioning
confidence: 99%